3(x-6)=54

Simple and best practice solution for 3(x-6)=54 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-6)=54 equation:


Simplifying
3(x + -6) = 54

Reorder the terms:
3(-6 + x) = 54
(-6 * 3 + x * 3) = 54
(-18 + 3x) = 54

Solving
-18 + 3x = 54

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18' to each side of the equation.
-18 + 18 + 3x = 54 + 18

Combine like terms: -18 + 18 = 0
0 + 3x = 54 + 18
3x = 54 + 18

Combine like terms: 54 + 18 = 72
3x = 72

Divide each side by '3'.
x = 24

Simplifying
x = 24

See similar equations:

| .16(24)+.04=.08(6+x) | | -17x+32=11x^2-17 | | 2y+4x+5=180 | | 9th-4+3(a-11)=23 | | 70=28+7x | | 20x+2y=-16 | | 2x+3=26 | | 2p-5r=q | | 20x-4=12x-20 | | 5*14-(2*1+4-1)= | | 8y-10y-y=-y | | 2(x+3)=5x+11 | | -13.4-0.5=10.1 | | .2x+5=22 | | 6.1+11.1=8s+7.1-7s | | 21-7K=-3K+4 | | X/5-2=0 | | 5*0-(2*0+4-0)= | | 16.7d=-3d+2 | | 4x-3y=5findy | | 4y=3y+33 | | 20-5s+4=-s-20 | | (90-x)=5x | | m^2+mn-56n^2=0 | | 5x=(90-x) | | -3n=29 | | -6g+20=-10g | | 43=-9-14x | | 12x+5=149 | | 10y-8y-y=0 | | x^2+8x=2x^2-40 | | .4x+4=40 |

Equations solver categories